Evaluation of performance of varieties and effect of different levels of harvesting of flower shoot on bulb production of LA hybrids in northern plain conditions - SINGH, M K; SINDHU, S S; DHAMA, A S (The Indian Journal of Agricultural Sciences, 2016)
A study was conducted to evaluate the performance and impact of different levels of harvesting of flower shoot on bulbs and bulblets production of LA hybrid lily cultivars Pavia, Ercolana and Brindisi in northern plain conditions. Field experiment was conducted at the Research Farm of the Division of Floriculture and Landscaping, Indian Agricultural Research Institute, New Delhi during 2014-15 and 2015-16. Uniform and healthy bulbs were planted in the month of November at a spacing of 15 × 15 cm between rows and bulbs under 50 % green shade net conditions in both the years. There is significant difference among the cultivars for days taken for flowering. The cv. Brindisi (70.10 days) has taken minimum days to flowering followed by Ercolana and Pavia. The maximum length and diameter of flower shoot 121.06 cm and 0.85 cm, respectively, was observed in cv. Pavia. Higher number of flower buds/shoot 6.13 was also recorded in cv. Pavia. The cv. Brindisi produced longer and bigger size flowers as compared to other cultivars. The maximum yield of bulbs and bulblets were recorded in disbudding plants followed by harvesting of flower shoot at 40 cm above the ground surface in cv. Pavia. The effect of harvesting flower shoots at 40 cm above the ground surface, resulted in better performance in the remaining parameters such as weight of bulbs per plant, diameter of bulb, and weight of bulblets per plant in all three cultivars. Harvesting of flower shoots at 40 cm is the best for bulb production in LA hybrid lily cultivation under northern plains conditions.